The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/08933189211041352
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Daily Emotional Labor on Health and Well-Being

Abstract: Emotional labor research largely focuses on client-facing occupations. However, employees across occupations engage in emotional labor when they perceive that specific types of emotional communication are required to align with organizational expectations. The current two-week daily survey study of 42 employees was conducted at a small website development company to examine relationships between employees’ emotional labor, physical health, and psychological well-being. Results indicated that daily emotional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Much of this research has focused on work itself, particular professions, well-being, and sustainability, and representing Miller et al's workplace emotion types in overlapping ways. Riforgiate et al [33] defined emotional labor as the "management of emotions as part of one's job performance" (p. 392) and explored its links to daily communication, physical health, and psychological well-being through a two-week-long diary study. They found that different forms of emotional labor might prove detrimental to workers' well-being.…”
Section: Emotions and Affective Gendered Organizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this research has focused on work itself, particular professions, well-being, and sustainability, and representing Miller et al's workplace emotion types in overlapping ways. Riforgiate et al [33] defined emotional labor as the "management of emotions as part of one's job performance" (p. 392) and explored its links to daily communication, physical health, and psychological well-being through a two-week-long diary study. They found that different forms of emotional labor might prove detrimental to workers' well-being.…”
Section: Emotions and Affective Gendered Organizingmentioning
confidence: 99%
“…you take a fair amount of unpleasant things and just deal with it." These comments constitute the marginalizing communication often found in STEM cultures [33].…”
Section: Women's Individual Strategiesmentioning
confidence: 99%
“…Interactive management research offers organizational communication scholars a tool to research diverse topics within the discipline of communication studies. For example, IMR would be particularly useful in domains such as the following: identifying ways to promote employee well-being (Riforgiate, et al, 2021); creating diverse, inclusive, and equitable workplaces (Ballard et al, 2020); facilitating organizational sensemaking in response to a crisis (Sahay & Dwyer, 2021); or promoting Corporate Social Responsibility through strategic planning based on stakeholders’ input (Maktoufi et al, 2020). Infusing these domains with IMR methods offers a methodological approach that promotes organizing through participants’ collective intelligence and communication.…”
Section: Imr In Organizational Settingsmentioning
confidence: 99%
“…Employees are not the only ones that may suffer unintended adverse outcomes associated with PIPs embedded within disciplinary structures due to the emotional nature of the exchange (Miller-Merrell, 2021). Managers who supervise the PIP process may also suffer poor work outcomes such as stress related burnout and emotional dissonance if they experience a conflict of emotion (Humphrey, 2012;Pugh et al, 2011;Riforgiate et al, 2022). As an occupational requirement, emotional labor requires the employee (in this example, the manager) to look and act in specific ways to meet the demands of the job (Grandey et al, 2015;Grandey, & Sayre, 2019;Humphrey et al, 2008).…”
Section: Performance Improvement Plansmentioning
confidence: 99%